Joy Bauer's superfood! : 150 recipes for eternal youth - Bauer, Joy (Abrams, 2020)
After reviewing countless studies and analyzing the eating habits of people around the world living the longest, healthiest lives, Joy uses the most nutritious ingredients to whip up super creative, crave-worthy food. The 150 recipes in Joy Bauer<U+2019>s Superfood! include everything from Buffalo wings to deep-dish pan pizza to salted caramel milkshakes to loaded nachos...and so much more. Imagine enjoying all these indulgent, delectable foods while boosting immunity, easing anxiety and stress, increasing energy, promoting longevity, and greatly improving your overall health. This book is the ultimate celebration of deliciousness and nutrient-rich recipes for eternal youth and vitality.